PERANCANGAN SISTEM INFORMSI E-JURNAL PADA PERGURUAN TINGGI BERBASIS WEB - Faridi Faridi; Peni Aripianti; Retno Widuri (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
echnology is something that cannot be separated in this modern era. With the advent of technology scholars and lecturers on the make in support of the process oflearning and teaching. Liabilities resulted in a scientific journal paper is a provision that is created in order improve the quality of education in Indonesia. Perguruan Tinggi Raharja is one of the educational institutions in the field of computer science always focuses oninnovative and creative in solving a problems. Aspects that support the Academic activity at one of them, namely in making scientific papers by scholars and lecturers that will serve as the scientific documentation. Therefore it needs a system to support the creation and publication of the journal. So it was created a system of "E-Jurnal" for simplify the search for clusters journal has also simplify the journal writing.